Fight like a girl. Volume 1, Learning curve - Pinckney, David (Action Lab Entertainment Inc, 2015)
Standing before a jury of nine gods, Amarosa pleads for a chance to risk her life and gain entry to the Wishing Well where she will fight her way through nine trials to claim her prize: a single wish that will save her terminally ill brother. Though she has some help, what she learns about herself here in the first four trials may be her only chance of survival.